Coral Reef Conditions in Bahowo Waters Tongkaina, Sub District Bunaken, Manado North Sulawesi - Podung, Thania Theresia; Roeroe, Kakaskasen A.; Paruntu, Carolus P.; Ompi, Medy; Schaduw, Joshian N. W.; Rondonuwu, Ari B. (Jurnal Ilmiah Platax, 2022)
Coral reefs are coastal ecosystems with the highest level of diversity with about one million species worldwide and are habitats for assemblages of millions of polyps that produce limestone to form their skeletons and develop into vast expanses of colonies. Corals are invertebrates belonging to the phylum Coelenterata (hollow animals) or Cnidaria. In order to preserve the coral reef ecosystem in the future in the Bahowo area, quantitative data is needed that can explain/describe the condition of coral reefs. The purpose of this study was to determine the condition of coral reefs, in this case, data on coral cover and associated biota in Bahowo waters. The data collection of this research used the UPT (Underwater Photo Transect) method. Analysis of the data in the form of research images using the CPCe (Coral Point Count with Excel extensions) application. The results of the analysis of the condition of coral reefs in Bahowo waters are in the damaged/bad category with live coral cover percentage data of 16.33%.Keywords: Live coral cover; Underwater photo transect (UPT); Coral reef condition; Bahowo watersAbstrakTerumbu karang merupakan ekosistem pesisir dengan tingkat keanekaragaman tertinggi dengan jumlah sekitar satu juta spesies di seluruh dunia dan merupakan habitat bagi kumpulan dari berjuta-juta hewan polip yang menghasilkan zat kapur membentuk skeletonnya dan berkembang menjadi hamparan koloni yang luas.  Karang adalah hewan tak bertulang belakang yang termasuk dalam filum Coelenterata (hewan berongga) atau Cnidaria.  Dalam rangka pelestarian ekosistem terumbu karang ke depan di daerah Bahowo, maka dibutuhkan data kuantitatif yang dapat menjelaskan/menggambarkan tentang kondisi terumbu karang.  Tujuan dari penelitian ini adalah untuk mengetahui kondisi terumbu karang, dalam hal ini data tutupan karang dan biota asosiasi di perairan Bahowo.  Pengambilan data penelitian ini menggunakan metode UPT (Underwater Photo Transect).  Analisis data berupa gambar penelitian menggunakan aplikasi CPCe (Coral Point Count with Excel extensions).  Hasil analisa kondisi terumbu karang di perairan Bahowo masuk dalam kategori rusak/buruk dengan data presentase tutupan karang hidup sebesar 16,33%.Kata kunci: Tutupan karang hidup; Underwater photo transect (UPT); Kondisi terumbu karang; Perairan Bahowo